COMBINING ABILITY ANALYSIS FOR GREEN FRUIT YIELD AND ITS COMPONENT TRAITS IN CHILLI (Capsicum annuum L.) - PATEL, BHAUMIK R; JI, NANAVATI; BR, PATEL; KB, KATHIRIYA; PATEL, DIXITA K (Innovare Journal of Agricultural Sciences, 2016)
ABSTRACT Objectives: Chilli is classified under self pollinated crops, natural cross pollination takes place up to the extent of 7 to 60 %.Â Â  Present study of combining ability analysis was conducted for identifying the superior parents for obtaining superior hybrid combinations in Chilli using male sterile lines. Methods: The present study was conducted at of Main Vegetable Research Station, Anand Agricultural University, Anand (Gujarat) during Kharif-Rabi 2011-2012 season with the objective of getting information on combining ability and nature of gene action for fruit yield and its component characters in chilli. Results: Parents viz., ACMS 4, 9907-9611 (B line), LCA 206, ACG 12 and RHRC PENDT were good general combiner for green fruit yield per plant and its related attributes. Conclusion: The estimates of specific combining ability effect indicated that cross combinations ACMS-4 x 9955-15R, CCA-4759 x LCA 206 and ACMS-8 x RHRC PENDT were significant for green fruit yield per plant and its important component characters and, therefore, these can be further exploited for selection of hybrids and transgressive segregants.